Maqosid al-Syaria'ah - Rahmawati, Elif Thoyyibah (Maliki Interdisciplinary Journal, 2024)
Islamic sharia is a religion that prioritizes the concept of rahmatan lil 'alamin, namely compassion for all creation, both humans and other living beings. Allah SWT has sent down rules and laws through the Prophet Muhammad PBUH as a guide for mankind in living life in the world. These rules and laws are designed to ensure the achievement of maslahah for the people. Meanwhile, maqashid sharia refers to a goal that leads to sharia, as a path to a source of life that provides benefits. Maqashid shari'ah serves as an important element in the goals of sharia, which plays a role in developing Islamic legal values to respond to social changes in society. Therefore, the study of maqashid shari'ah is very useful as an analytical tool to improve the law by considering the changing social conditions. In this context, there are three principles that are components of the concept of maslahah, namely freedom, security, and equality.